Women's Awareness and Knowledge of Abortion Laws: A Systematic Review. - Anisa R Assifi; Blair Berger; Özge Tunçalp; Rajat Khosla; Bela Ganatra (PLoS ONE)
Background Incorrect knowledge of laws may affect how women enter the health system or seek services, and it likely contributes to the disconnect between official laws and practical applications of the laws that influence women's access to safe, legal abortion services. Objective To provide a synthesis of evidence of women's awareness and knowledge of the legal status of abortion in their country, and the accuracy of women's knowledge on specific legal grounds and restrictions outlined in a country's abortion law. Methods A systematic search was carried for articles published between 1980-2015. Quantitative, mixed-method data collection, and objectives related to women's awareness or knowledge of the abortion law was included. Full texts were assessed, and data extraction done by a single reviewer. Final inclusion for analysis was assessed by two reviewers. The results were synthesised into tables, using narrative synthesis. Results Of the original 3,126 articles, and 16 hand searched citations, 24 studies were included for analysis. Women's correct general awareness and knowledge of the legal status was less than 50% in nine studies. In six studies, knowledge of legalization/liberalisation ranged between 32.3%-68.2%. Correct knowledge of abortion on the grounds of rape ranged from 12.8%-98%, while in the case of incest, ranged from 9.8%-64.5%. Abortion on the grounds of fetal impairment and gestational limits, varied widely from 7%-94% and 0%-89.5% respectively. Conclusion This systematic review synthesizes literature on women's awareness and knowledge of the abortion law in their own context. The findings show that correct general awareness and knowledge of the abortion law and legal grounds and restrictions amongst women was limited, even in countries where the laws were liberal. Thus, interventions to disseminate accurate information on the legal context are necessary.